The Relationship between Lifelong Learning and Attitudes towards the Teaching Profession of Pre-service Teachers - Kula Sultan Selen (Sciendo, 2023)
Introduction: The purpose of this study was to examine the relationship between lifelong learning (LL) and attitudes towards the teaching profession (ATTP) of pre-service teachers. LL and ATTP of pre-service teachers were compared in terms of gender, perceived success level and reading frequency variables.